The Politics of Drugs : Perceptions, Power and Policies - MacGregor, Susanne (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book explores the complexities of drugs policy in Britain, contradicting the over simplified representation found in the public sphere. It focuses on developments in Britain since the Misuse of Drugs Act of 1971, covering debates at national level and local experiences set in international and European context, emphasizing the interconnectivity between people and countries in this global age. Several institutions and networks are examined to illustrate how they shape the policy process as vessels for ideas and interests and as spaces for individual action. MacGregor discusses arguments around drug policy reform, in particular the role of politicians, the media and advocacy organizations. Her aim is to encourage a more open and intelligent conversation on drugs policy and to question whether the institutional architecture in place is fit for purpose given the great increase of substances available and the underlying variety of conditions and interests currently competing for attention and resources. The is a must read for all scholars of Politics, Medicine and Social Science interested in the current debate raging around British Drug Policy.- Resumé vydavatel
Keywords: protidrogová politika -- Velká Británie; drogy -- Velká Británie; drug and narcotic control -- Great Britain; drugs of abuse -- Great Britain; elektronické knihy; monografie; electronic books; monographs